Visual pursuit of one's own face in disorders of consciousness: a quantitative analysis. (15th October 2018) - Trojano, Luigi; Moretta, Pasquale; Masotta, Orsola; Loreto, Vincenzo; Estraneo, Anna
ABSTRACT: Background : Eye behaviour is important to distinguish minimally conscious state (MCS) from vegetative state (VS). Objective : To search for conditions most suitable to characterize patients in MCS and in VS on quantitative assessment of visual tracking. Design : This is a cross-sectional study. Participants : In total, 20 patients in VS, 13 in MCS plus and 11 in MCS minus participated in this study. Setting : Neurorehabilitation Unit. Methods : Evaluation of eye behaviour was performed by infrared system; stimuli were represented by a red circle, a picture of a patient's own face and a picture of an unfamiliar face, slowly moving on a personal computer (PC) monitor. Visual tracking on the horizontal and vertical axes was compared. Main outcome measures : The main outcome measures were proportion of on-target fixations and mean fixation duration. Results : The proportion of on-target fixations differed as a function of the stimulus in patients in MCS plus but not in other groups. Own face and unfamiliar face elicited a similar proportion of on-target fixations. Tracking along the horizontal axis was more accurate than that along the vertical axis in patients in both MCS plus and MCS minus . Fixation duration did not differ among the three groups. Conclusions : Horizontal visual tracking of salient stimuli seems particularly suitable for eliciting on-target fixations. Quantitative assessment of visual tracking can complement clinical evaluation for reducing diagnostic uncertainty between patients in MCS or VS.